The evolution of the Cercopithecini: a (post)modern synthesis. Issue 6 (21st December 2017) - Lo Bianco, Stefania; Masters, Judith C.; Sineo, Luca
Abstract: The Cercopithecini, or African guenon monkeys, are one of the most diverse clades of living primates and comprise the most species‐rich clade of Catarrhini. Species identity is announced by flamboyant coloration of the facial and genital regions and, more cryptically, by vigorous chromosomal rearrangements among taxa. Beneath the skin, however, these animals are skeletally conservative and show low levels of genetic sequence divergence consonant with recent divergence between congeneric species. The guenons clearly demonstrate that morphological, cytogenetic, and reproductive differentiation proceed at different rates during speciation. We review diverse kinds of data in an effort to understand this conundrum.